Discover the Alchemist Within : Taking the First Step Towards Personal Growth. - V., Kartikeyan (SAGE Publications, 2018)
A creative and path-breaking effort to connect lessons from the world of Karnatik Music to effectiveness in human processes and well-being of human beings and systems.